METAPHOR IN NOVEL SEPATU DAHLAN BY KHRISNA PABICHRA - Oktariyani Oktariyani (LPPM Universitas Bina Sarana Informatika, 2018)
METAPHOR IN NOVEL “ SEPATU DAHLAN” BY KHRISNA PABICHARA(STYLISTIC ANALYSIS) BY OKTARIYANIoktariyani.yani@yahoo.co.idUNIVERSITAS NAHDATUL ULAMA LAMPUNGABSTRACT. The purpose of this study is to get deep knowledge of metaphor; (1) based on the creation of meaning, ( 2 ) based on images, ( 3 ) based on the meaning of field ecosystem. Describe the functions of the metaphor in the novel Sepatu Dahlan by Krishna Pabichara. The method used this study is content analysis. The approach of this study is stylistic that is part of a qualitative approach. Steps of this research are (a) intensive reading and repeat reading novel that will be research, (b) make notes every phrase, clause, or sentence of metaphor in the novel (c) identify some things there are in objective of this research and (d) do the analysis and do data interpretation.The results of the data analysis found 48 sentences included in the category of metaphor is based on the creation of meaning, which consists of 8 sentences of blank symbols, 28 sentences of natural symbols and private symbols 16 sentences. Found 34 sentences were included in the category of metaphors based on images, which consists of visual 14 sentences, 14 sentences auditory. Taklitis 7 sentences, gustative 2 sentences, images olfaction 1 sentence. Found 55 sentences which are categorized based on the ecosystem metaphor meaning field, which consists of 5 sentences being, Cosmos 10 sentences, 12 sentences energy, to the category of substance is not found in the novel. Terrestrial 3 sentences, the object 3 sentences, living 5 sentences, animate 7 sentences, 10 sentences of a human. While the function of metaphor in the novel of Sepatu Dahlan includes expression language functions and communication of speech acts consisting of illocutionary and perlocutionary. Keywords: Metaphor, stylistic, novel, kinds of metaphor, the function of metaphor.